EVALUATION OF MOTOR FUNCTION IMPROVEMENT AFTER INTERVENTION IN CHILDREN WITH ENCEPHALITIS SEQUELAE ACCORDING TO TRADITIONAL MEDICINE SYNDROME PATTERNS AT THE NATIONAL HOSPITAL OF TRADITIONAL MEDICINE (Vietnam Journal of Community Medicine, 2026)
Objectives: Evaluating the effectiveness of motor rehabilitation in children with sequelae of encephalitis according to Traditional Medicine.Subjectives: Sixty pediatric patients aged ≤ 6 years were diagnosed with sequelae of encephalitis after the acute phase, including motor and mental sequelae with manifestations of motor paralysisMethods: Clinical intervention, pre- and post-treatment comparison, without a control group. Pediatric patients were classified according to two Traditional Medicine disease types: Yin deficiency and Qi and Blood deficiency. The children underwent a 6-week course of massage and acupressure combined with nursing care. Assessment criteria included the Henry scale and developmental index (DQ) according to the Denver II test.Results: Before intervention, the Yin deficiency type was predominant (73.3%); the Yin deficiency type had milder paralysis than the Qi and Blood deficiency type (grade IV paralysis accounted for 13.6% compared to 62.5%). After 6 weeks of intervention, motor function improved significantly in both groups (p < 0.05). The Yin deficiency type showed better recovery: the percentage of gross and fine motor development indices returning to normal levels was 45.5%, while in the Qi and Blood deficiency type it was 37.5% and 12.5%, respectivelyConclusions: Acupressure combined with nursing care has a good recovery rate in both disease types, with the Yin deficiency type having a better prognosis for functional recovery and developmental indicators compared to the Qi and Blood deficiency type
Keywords: Sequelae of encephalitis, disease types according to Traditional Medicine, acupressure, motor rehabilitation